A Novel Automatic Water Autosampler Operated From UAVs for Determining Dissolved Trace Elements - Sparaventi, Erica; Rodríguez-Romero, Araceli; Navarro, Gabriel; Tovar-Sánchez, Antonio (Frontiers in Marine Science, 2022)
Monitoring water systems under extreme conditions or in remote areas poses a risk to scientists and staff involved, and can also result in disturbances to the local flora and fauna. In order to overcome these limitations, new techniques are being developed with the aim to gain more insight into how geochemical pathways of trace elements regulate the functioning of the ocean. Here, we present the first trace metals and inorganic nutrients concentrations measured in dissolved (<0.22 µm) surface water samples collected in the Antarctic by using an Automatic Water Autosampler (AWA) system onboard an unmanned aerial vehicle (UAV). The AWA system has been used to chemically quantify the composition of the water masses (lake and coastal water) of Deception Island (South Shetland Islands, Antarctica), with, for example, Pb values ranging from 0.01 to 0.25 nM in seawater and 1.20 to 2.11 nM in lake water. The results demonstrate the effectiveness of the AWA system in environmental studies that require the sampling of trace metals and nutrients without sample contamination.